1972
DOI: 10.1111/j.1399-3054.1972.tb03583.x
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Populus tremula to Picloram and Other Translocated Herbicides

Abstract: Whole aspen plants and isolated aspen root segments were three to ten times more sensitive to the growth‐inhibitory and toxic effects of picloram than to those of 2,4‐D, 2,4,5‐T and dicamba. The activity of picloram in the inhibition of root growth was about ten times higher than that of 2,4‐D and dicamba when tbe substances were added to the nutrient solution. Epinastic responses indicated a very rapid translocation of picioram from the roots to the growing shoot parts. When the herbicides were applied to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1977
1977
1988
1988

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…ELIASSON (1972) had shown that the root and shoot growth of aspen was very sensitive to picloram at concentrations of lO-'-lO^ "M.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ELIASSON (1972) had shown that the root and shoot growth of aspen was very sensitive to picloram at concentrations of lO-'-lO^ "M.…”
Section: Discussionmentioning
confidence: 99%
“…By short, direct exposure of buds and leaves to the extremely low concentrations affecting cultured cells, we minimized translocation effects (ELIASSON 1972) and could test the sensitivity of different stages to picloram (Fig. 4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation